The writing processes underpinning wellbeing: Insight and emotional clarity in poetic autoethnography and freewriting - Hanauer, David I. (Frontiers in Communication, 2022)
Investigations of the expressive writing paradigm have shown that writing about one’s experiences have positive effects on wellbeing. Understanding the writing processes facilitating self-discovery which underpin these positive outcomes is currently lacking. Prior research has suggested two writing processes that can lead to discovery: 1) Knowledge Constituting involving the fast synthesis of verbal and non-verbal memory traces into text; and 2) Knowledge Transforming involving controlled engagement with written text for revision. Here two genres - autoethnographic poetry and freewriting – were studied as they manifest a different pattern design for Knowledge Constituting and Knowledge Transforming. 117, L1 English speaking participants from 3 northwestern universities in the US completed a two-stage, genre specific writing process. Participants were randomly assigned to a writing condition. Poetry writers first did a Knowledge Constituting writing task followed by a Knowledge Transforming task. Freewriters repeated a Knowledge Constituting task. Participants completed insight and emotional clarity scales after stage one and stage two. Data was analyzed using a two-way repeated measures ANOVA with one between (writing condition) and one within subject (time of prompt) variables. Descriptive results show that it is the Knowledge Constituting process which elicits high levels of insight and emotional clarity for both genres at the first time point. Knowledge Transforming at time-point 2 significantly reduced insight. While Knowledge Constituting at time-point 2 significantly increased emotional clarity. The results support the position that it is the Knowledge Constituting writing process which facilitates self-discovery and underpins writing-for-wellbeing outcomes.